1941
DOI: 10.1002/hlca.19410240186
|View full text |Cite
|
Sign up to set email alerts
|

Über die enzymatische Oxydation des Carotins

Abstract: 1. Die Wirksamkeit des Enzyms aus der Sojabohne, das in Gegenwart eines ungesättigten Fettes oder einer ungesättigten Fettsäure die Oxydation von Carotin bewirkt, bleibt nach 24‐stündiger Dialyse erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1941
1941
1948
1948

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Unsaturated fatty acids.-The oxidation of compounds of the oleic acid type by lipoxidase from soy beans was investigated independently by Sumner (143) and Siillmann (144,145). In many respects these investigations complement each other and may be reported jointly.…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsaturated fatty acids.-The oxidation of compounds of the oleic acid type by lipoxidase from soy beans was investigated independently by Sumner (143) and Siillmann (144,145). In many respects these investigations complement each other and may be reported jointly.…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…It seems from the oxygen uptake that only one of the two double bonds in linoleic acid and two of the three in linolenic acid were oxidized. Indications were found that carbonyl compounds were among the oxidation products(145) . The coupled oxidation of carotene occurs only concomitantly with fatty acid oxi dation although large amounts of peroxide may accumulate.…”
mentioning
confidence: 99%